Dietary intake and associations with myopia in Singapore children. (3rd December 2021) - Li, Mijie; Tan, Chuen‐Seng; Foo, Li‐Lian; Sugianto, Ray; Toh, Jia Ying; Sun, Chen‐Hsin; Yap, Fabian; Sabanayagam, Charumathi; Chong, Foong‐Fong Mary; Saw, Seang‐Mei
Abstract: Purpose: To evaluate associations of dietary factors with myopia, spherical equivalent refractive error (SE) and axial length (AL) in children at age 9 from the Growing Up in Singapore Towards healthy Outcomes (GUSTO) birth cohort. Methods: We included 467 multi‐ethnic children (933 eyes) who participated in the GUSTO prospective birth cohort and were delivered in two major hospitals in Singapore (2009–2010). At the 9‐year visit, we assessed the 6‐year incidence of myopia (between ages 3 to 9), cycloplegic SE and AL in children without myopia (SE ≤ −0.5 D in either eye) at the 3‐year visit. Using a validated 112‐item food frequency questionnaire, parents reported each child's average daily intake of dietary factors (nutrients and food groups) in the past month. Paired eyes were analysed using Generalised Estimating Equations with multivariable logistic or linear regression. Bonferroni corrections were applied, correcting for multiple comparisons between the 13 nutrients ( p  < 0.004) or 8 food groups ( p  < 0.006) and each outcome. Results: In children aged 9 years (51.0% boys; 56.3% Chinese), the 6‐year incidence of myopia was 35.5%. Overall, the mean (SD) SE and AL were −0.3 (1.7) D and 23.4 (1.0) mm, respectively. In multivariable regression, macronutrients or micronutrients were not associated with incident myopia ( p  ≥ 0.004 for all), adjusting for total energy, gender, ethnicity, time outdoors, near‐work and the number of myopic parents (additionally child's height for outcome AL). Similarly, all food groups (including refined grains, sugar‐sweetened beverages, protein foods, fruits and vegetables) were not associated with incident myopia ( p  ≥ 0.006 for all). Additionally, none of the nutrients ( p  ≥ 0.004 for all) or food groups ( p  ≥ 0.006 for all) were associated with SE or AL. Conclusions: Our study findings of no significant association between specific nutrients or food groups and incident myopia or SE or AL suggest that diet may not be associated with myopia in children aged 9 years. Well‐conducted prospective studies in other populations may clarify the association.